2009
DOI: 10.1002/pbc.22323
|View full text |Cite
|
Sign up to set email alerts
|

MGMT as a potential stratification marker in relapsed high‐grade glioma of children: The HIT‐GBM experience

Abstract: DNA methylation, but not protein expression of MGMT was associated with an increased median EFS and OS of children with relapsed HGG. MGMT methylation status warrants prospective evaluation as a stratification marker for children with HGG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 37 publications
1
4
0
1
Order By: Relevance
“…Similar to the findings in adult glioma patients, MGMT promoter methylation [110], and reduced MGMT protein expression [100] have been reported to be associated with longer survival of pediatric malignant glioma patients. In ependymal tumors, MGMT promoter methylation is less common when compared with diffuse astrocytic and oligodendroglial tumors [13, 74].…”
Section: Mgmt Hypermethylation As a Prognostic Or Predictive Marker Isupporting
confidence: 74%
“…Similar to the findings in adult glioma patients, MGMT promoter methylation [110], and reduced MGMT protein expression [100] have been reported to be associated with longer survival of pediatric malignant glioma patients. In ependymal tumors, MGMT promoter methylation is less common when compared with diffuse astrocytic and oligodendroglial tumors [13, 74].…”
Section: Mgmt Hypermethylation As a Prognostic Or Predictive Marker Isupporting
confidence: 74%
“…The effectiveness of temozolomide, alone or combination with radiation and/or other agents, in pediatric gliomas remains uncertain (24) (27). However, none of these studies compared the MGMT status between pediatric and adult gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…Another small retrospective study (N ¼ 24) reported that 50 % of pediatric glioblastoma patients had MGMT promoter methylation but did not provide correlation with clinical outcome (Srivastava et al 2010). One retrospective study of a small set of pediatric patients (N ¼ 24) who were more uniformly treated by enrollment in the German HIT-GBM trial showed that MGMT promoter methylation was seen in 77 % of patients and was associated with longer event-free survival compared with the unmethylated cohort whereas MGMT protein levels did not exhibit this correlation (Schlosser et al 2010). However, other retrospective studies have reported 0-30 % cases of high grade gliomas with MGMT promoter methylation (Buttarelli et al 2010;Fassan et al 2011;Lee et al 2011) emphasizing the need for analysis of a larger patient population to accurately establish the true proportion of pediatric gliomas with this finding.…”
Section: Epigenetics In Cancermentioning
confidence: 94%